Method for prevention and control of spontaneous combustion of coal seam and its application in mining field - Lu, Wei; Cao, Ying-Jiazi; Tien, Jerry C. (International journal of mining science and technology, 2017)
Spontaneous combustion of coal seam has been and continues to be a big problem in coal mines. It could pose great threat to the safety of the whole mine and all miners, especially when it occurs in or nearby coal mines. Besides, environment of area surrounded mines during combustion can be threatened where large amount of toxic gases including CO2, CO, SO2 and H2S can be leased by fire in mine. Hence, it is important and significant for scholars to study the controlling and preventing of the coal seam fire. In this paper, the complicated reasons for the occurrence and development of spontaneous combustion in coal seam are analysed and different models under various air leakage situations are built as well. Based on the model and approximately calculation, the difficulty of fire extinguishment in coal seam is pointed out as the difficulty and poor effect to remove the large amount of heat released. Detailed measurements about backfilling and case analyses are also provided on the basis of the recent ten years' practice of controlling spontaneous combustion in coal seams in China. A technical fire prevention and control method has been concluded as five steps including detection, prevention, sealing, injection and pressure adjustment. However, various backfill materials require different application and environmental factors, so in this paper, analyses and discussion about the effect and engineering application of prevention of spontaneous combustion are provided according to different backfilling technologies and methods. Once the aforementioned fire prevention can be widely applied and regulated in mines, green mining will be achievable concerning mine fire prevention and control.